Patterns and severity of neuromuscular transmission failure in seronegative myasthenia gravis - Nemoto, Y (BMJ Group, 2005)
Objectives: To compare the clinical and electrophysiological features of myasthenia gravis (MG) patients with (seropositive) or without (seronegative) antibodies to acetylcholine receptor. To investigate whether antibodies to muscle specific kinase (MuSK) and ryanodine receptor (RyR) are associated with particular features. Methods: Clinical profiles and single fibre electromyography (SFEMG) in the extensor digitorum communis (EDC) were reviewed in consecutive 57 seropositive and 13 seronegative patients. Antibodies to MuSK and RyR were measured by immunoassays. Results: Of the 13 seronegative patients, four (31%) were positive for MuSK antibodies and seven (54%) were positive for RyR antibodies, including all four MuSK positive patients. Clinical features were similar at presentation for seropositive and seronegative patients, but MuSK positive patients frequently developed myasthenic crises. Despite the similar clinical severities at the time of examination, the proportion with positive jitter (93% of seropositive patients, 50% of MuSK positive patients, and 44% of MuSK negative patients) and the extent of jitter (mean consecutive difference: 76 µs in seropositive patients, 36 µs in MuSK positive patients, and 30 µs in MuSK negative patients) were less in seronegative MG patients compared with seropositive MG patients. Conclusions: Seronegative MG is heterogeneous with respect to the presence of antibodies to MuSK. Impairment of neuromuscular synaptic transmission in EDC is less marked in seronegative than seropositive MG despite the similar clinical severity. This discrepancy may partly reflect the distribution of affected muscles in seronegative patients, but it is possible that other factors, such as impaired excitation-contraction coupling resulting from RyR antibodies, contribute to the clinical phenotype.